1997
DOI: 10.1136/hrt.77.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged asystole induced by head up tilt test. Report of four cases and brief review of the prognostic significance and medical management.

Abstract: Head up tilt is an established test for assessing patients with vasovagal syncope. Prolonged asystole during the test has previously been reported in patients suffering from the malignant form of this syndrome. Little is known about the prognostic significance of this response and there is no consensus about the optimum treatment. Four such patients are reported who were treated pharmacologically. During follow up they remained free from major events and their symptoms were welil controiled. Conservative manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…In a few papers [16,30] a greater severity of symptoms (as assessed by the frequency of seizures or injury during spontaneous episodes) was observed before the initial evaluation in patients with tilt-induced asystole. However, in many other studies this finding was not confirmed and the clinical outcome of asystolic patients after tilt evaluation appeared to be not different from that of non-asystolic patients [27][28][29]31,32] . Indeed, the incidence of new syncopal events, in a pooled analysis, was 12% among 105 patients with tilt-induced asystole during a follow-up of 9 to 25 months (mean, 19) [ [16][17][18][27][28][29][30][31][32] compared to 35% among 218 control patients without asystole during a follow-up of 16 to 36 months (mean, 24) [28,29] .…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…In a few papers [16,30] a greater severity of symptoms (as assessed by the frequency of seizures or injury during spontaneous episodes) was observed before the initial evaluation in patients with tilt-induced asystole. However, in many other studies this finding was not confirmed and the clinical outcome of asystolic patients after tilt evaluation appeared to be not different from that of non-asystolic patients [27][28][29]31,32] . Indeed, the incidence of new syncopal events, in a pooled analysis, was 12% among 105 patients with tilt-induced asystole during a follow-up of 9 to 25 months (mean, 19) [ [16][17][18][27][28][29][30][31][32] compared to 35% among 218 control patients without asystole during a follow-up of 16 to 36 months (mean, 24) [28,29] .…”
mentioning
confidence: 97%
“…Up to now only a few papers have examined the topic of a tilt-induced asystole [15][16][17][18][27][28][29][30][31][32] . On the whole, 714 patients with a positive response to head-up tilt testing have been studied.…”
mentioning
confidence: 99%
See 3 more Smart Citations